Moveable type : book history in India - Gupta, Abhijit; Chakravorty, Swapan (Ranikhet, Uttaranchal : Permanent Black, 2008)
Contributed articles.
Includes bibliographical references and index.
Keywords: Books -- India -- History; Book industries and trade -- India -- History; Books and reading -- India -- History